Resource recovery and circular economy from organic solid waste using aerobic and anaerobic digestion technologies - Wainaina, Steven; Awasthi, Mukesh Kumar; Sarsaiya, Surendra; Chen, Hongyu; Singh, Ekta; Kumar, Aman; Ravindran, B.; Awasthi, Sanjeev Kumar; Liu, Tao; Duan, Yumin; Kumar, Sunil; Zhang, Zengqiang; et al. (Bioresource technology, 2020)
•Reviewed resource recovery from organic solid waste towards bio-circular economy.•Aerobic and anaerobic digestion technology: a sustainable approach for biorefinery.•Organic solid waste: a potential biorefinery and bio-economy option. With the inevitable rise in human population, resource recovery from waste stream is becoming important for a sustainable economy, conservation of the ecosystem as well as for reducing the dependence on the finite natural resources. In this regard, a bio-based circular economy considers organic wastes and residues as potential resources that can be utilized to supply chemicals, nutrients, and fuels needed by mankind. This review explored the role of aerobic and anaerobic digestion technologies for the advancement of a bio-based circular society. The developed routes within the anaerobic digestion domain, such as the production of biogas and other high-value chemicals (volatile fatty acids) were discussed. The potential to recover important nutrients, such as nitrogen through composting, was also addressed. An emphasis was made on the innovative models for improved economics and process performance, which include co-digestion of various organic solid wastes, recovery of multiple bio-products, and integrated bioprocesses.